2020
DOI: 10.3390/ijms21051763
|View full text |Cite
|
Sign up to set email alerts
|

Lipofundin MCT/LCT Inhibits Levcromakalim-Induced Vasodilation by Inhibiting Endothelial Nitric Oxide Release

Abstract: The goal of this study was to examine the effect of lipid emulsion on the vasodilation induced by ATP-sensitive potassium (KATP) channels in isolated rat aortae and the underlying mechanism. The effects of Intralipid, containing 100% long-chain fatty acids, and Lipofundin MCT/LCT, containing 50% long-chain fatty acids plus 50% medium-chain fatty acids, on the vasodilation induced by levcromakalim in endothelium-intact aorta with or without NW-nitro-L-arginine methyl ester (L-NAME) and in endothelium-denuded ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
(73 reference statements)
1
14
0
Order By: Relevance
“…Similar to the findings of previous reports, LE (1%) enhanced the DMT-induced maximal contraction of the endothelium-intact aorta ( Figure 2 A), whereas L-NAME pretreatment abolished LE (1%)-mediated enhancement of the DMT-induced contraction of the endothelium-intact aorta ( Figure 3 A), suggesting that LE (1%)-mediated enhancement of the DMT-induced contraction was caused by inhibition of NO synthesis, which seemed to be associated with the decreased concentration of DMT caused by LE [ 17 , 20 ]. As LE alone reduces NO synthesis, the complete separation of indirect (reduction of DMT concentration) and direct effect (direct inhibition of DMT-induced eNOS phosphorylation) of LE contributing to the inhibition of NO synthesis induced by DMT, was very difficult to achieve in our study ( Figure 10 ) [ 17 , 21 ]. The high concentration of LE (3%) decreased DMT-induced contraction of the endothelium-denuded aorta and endothelium-intact aorta pretreated with L-NAME ( Figure 2 B and Figure 3 A,B).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the findings of previous reports, LE (1%) enhanced the DMT-induced maximal contraction of the endothelium-intact aorta ( Figure 2 A), whereas L-NAME pretreatment abolished LE (1%)-mediated enhancement of the DMT-induced contraction of the endothelium-intact aorta ( Figure 3 A), suggesting that LE (1%)-mediated enhancement of the DMT-induced contraction was caused by inhibition of NO synthesis, which seemed to be associated with the decreased concentration of DMT caused by LE [ 17 , 20 ]. As LE alone reduces NO synthesis, the complete separation of indirect (reduction of DMT concentration) and direct effect (direct inhibition of DMT-induced eNOS phosphorylation) of LE contributing to the inhibition of NO synthesis induced by DMT, was very difficult to achieve in our study ( Figure 10 ) [ 17 , 21 ]. The high concentration of LE (3%) decreased DMT-induced contraction of the endothelium-denuded aorta and endothelium-intact aorta pretreated with L-NAME ( Figure 2 B and Figure 3 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, similar to the LE-mediated enhancement of the DMT-induced contraction in the endothelium-intact aorta ( Figure 2 A and Figure 3 A) via inhibition of NO synthesis, LE reverses both the increased stimulatory eNOS (Ser1177) phosphorylation and the decreased inhibitory eNOS (Thr495) phosphorylation induced by DMT ( Figure 6 A,B), leading to decreased NO release and cGMP formation ( Figure 5 ). This effect seems to be mainly associated with the absorption of DMT by LE and partially caused by direct inhibition of NO release ( Figure 10 ) because LE alone decreases cGMP formation [ 21 ]. Src kinase inhibitor PP2 attenuated the increased stimulatory eNOS (Ser1177) phosphorylation and the decreased inhibitory eNOS (Thr495) phosphorylation induced by DMT ( Figure 8 A,B), suggesting that DMT-induced eNOS (Ser1177 and Thr495) phosphorylation is mediated by Src kinase.…”
Section: Discussionmentioning
confidence: 99%
“…However, other in vitro studies have suggested that minoxidil-induced vasodilation is endothelium independent (Spokas et al 1983;Meisheri et al 1988). Hence, the role of endothelial NO on minoxidil-induced vasodilation seems controversial (Spokas et al 1983;Meisheri et al 1988;Kontos and Wei 1996;Kinoshita et al 1999;Lee et al 2020). Therefore, we investigated whether minoxidil-induced vasodilation is mediated by endothelial NO.…”
Section: Introductionmentioning
confidence: 90%
“…Male Sprague-Dawley rats (body weight: 250-300 g) were anesthetized with 100% carbon dioxide, administered via a small hole in the rat cage. Isolated rat aorta was used for measuring isometric tension; it was prepared as described previously (Lee et al 2020). The rat thoracic cavity was exposed and the descending thoracic rat aorta of each rat was removed from the thoracic cavity and immersed in Krebs solution, composed of NaCl (118 mM), NaHCO 3 (25 mM), glucose (11 mM), KCl (4.7 mM), CaCl 2 (2.4 mM), MgSO 4 (1.2 mM), and KH 2 PO 4 (1.2 mM).…”
Section: Preparation Of Isolated Rat Aorta and Isometric Tension Measmentioning
confidence: 99%
See 1 more Smart Citation